Strategi Kesantunan dan Ketidaksantunan dalam Tindak Tutur Direktif Guru - Sumarti Sumarti (Aksara: Jurnal Bahasa dan Sastra, 2015)
Strategy directive speech acts teachers (STTDG) in learning impact on student affective color. An attempt to "keep face" that correlates with the basic needs of students, ie, love and self-esteem should be considered a teacher for learning is effective and fun. By using descriptive-phenomenological research design, data collection techniques of observation, tapping records, questionnaires, and interviews; and conducted domain analysis, taxonomy, and heuristics to STTDG in learning Indonesian in SMP obtained the following results. The strategy of politeness used in speech acts directive teachers include (1) to intensify attention hearer, (2) pay attention to the hearer, (3) praise, (4) pay attention to the needs hearer, (5) use the greeting, (6) seek agreement, (7) avoid disagreements, (8) promised reward, (9) include the speaker and hearer in activities, (10) using a joke, while the strategy ketidaksantunan consisting of (a) speech does not directly snide, (b ) greet with interjections, (c) to compare, and (d) there is an element chided.Keywords: strategy directive speech acts, affective color, politeness and impoliteness strategies